Theories of Motivation to Support the Needs of All Learners (LEARNing Landscapes, 2023)
The increasing number of students requiring special education support is a plea for students to be taught the way they learn best. Through the authentic educational experiences of a diverse family, this paper explores the impact of theories of motivation to support all learners. This exploration proposes that educators may be able to support the needs of all learners in inclusive classrooms by integrating the theories of self-efficacy, self-determination, and implicit theories of intelligence.
Keywords: motivation; inclusion; self-efficacy; self-determination; diversity